2014
DOI: 10.1111/hepr.12322
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of natural killer cell activity by pegylated interferon‐alpha/ribavirin therapy in chronic hepatitis C patient

Abstract: PEG IFN/RBV therapy in CHC patients could improve NK activity by increasing the frequency of CD56(bright) NK cells in SVR patients. Our study also revealed that eradication of HCV could restore NK-cell activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In this study, the frequency of CD56 dim NK cells was revealed to be increased by DAA therapy. However, PEG/RBV therapy induced an increase in the frequency of CD56 bright NK cells . Therefore, PEG/RBV therapy might affect the increase in the frequency of CD56 bright NK cells.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In this study, the frequency of CD56 dim NK cells was revealed to be increased by DAA therapy. However, PEG/RBV therapy induced an increase in the frequency of CD56 bright NK cells . Therefore, PEG/RBV therapy might affect the increase in the frequency of CD56 bright NK cells.…”
Section: Discussionmentioning
confidence: 98%
“…Hepatitis C virus infection is reported to reduce NK cell activity . We have already reported that PEG/RBV therapy could restore NK cell activity in CH(C) patients with SVR . The restoration of NK cell activity was speculated to be due to a decline of HCV load by the therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations